(untitled) (The Review of Diabetic Studies, 2025)
Background: The co-management of surgical patients by internal medicine physicians and general surgeons has been shown to be a promising strategy to improve patient outcomes. Although previous studies have shown a reduction in hospital length of stay and postoperative complications in a single-center setting, no systematic synthesis of this data exists. This systematic review aims to fill this information gap. Objectives: This systematic review aims to assess whether a structured co-management model between internal medicine and surgery specialists can reduce hospital length of stay and overall complication rates compared to conventional surgical practice. This review will include studies published between 2020 and 2026. Methods: This systematic review will follow the PRISMA 2020 guidelines and include a systematic search of PubMed/MEDLINE, Embase, CINAHL, and the Cochrane Library. Studies will be included if they reported hospital length of stay and/or complication rates in adult patients receiving a structured co-management model between an internal medicine and a general surgeon. Two authors will independently review 921 studies; 10 studies with 5,604 patients will be included in this systematic review. The quality of included studies will be assessed with the Cochrane RoB 2 tool for randomized controlled trials and ROBINS-I for observational studies. Results: The pooled weighted mean difference was -2.08 days (95% CI: -2.61 to -1.54; p < 0.001) in LOS, showing the benefits of co-management. The overall complications were significantly reduced among patients who underwent co-management (OR 0.56, 95% CI: 0.47-0.67; p < 0.001). The results of the subgroup analysis showed the benefits of co-management in various geographical settings and surgical subspecialties. The heterogeneity was moderate (I² 42-58%). Conclusions: The results of the study established a positive correlation between Collaborative IM-Surgery Co-Management and reduced hospital LOS as well as complications. Healthcare systems are encouraged to adopt co-management as a model of care delivery.